2018
DOI: 10.1055/s-0038-1635116
|View full text |Cite
|
Sign up to set email alerts
|

Liposuction Treatment of Lymphedema

Abstract: In the Western world, lymphedema most commonly occurs following treatment of cancer. Limb reductions have been reported utilizing various conservative therapies including manual lymph and pressure therapy, as well as by microsurgical reconstruction involving lymphovenous shunts and transplantation of lymph vessels or nodes. Failure of these conservative and surgical treatments to provide complete reduction in patients with long-standing pronounced lymphedema is due to the persistence of excess newly formed sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 41 publications
0
58
0
4
Order By: Relevance
“…These characteristics significantly reduce the incidence of erysipelas and cellulitis (131). The complications from liposuction are limited, with a very low incidence rate; paresthesia of the skin is the most typical complication and fades away within 3-6 months (132), and fibrous tissue increases in some cases, specifically in women with a male distribution of body fat (132). The characteristics of current treatment scenarios for lymphedema are summarized in Table III.…”
Section: Treatmentmentioning
confidence: 99%
“…These characteristics significantly reduce the incidence of erysipelas and cellulitis (131). The complications from liposuction are limited, with a very low incidence rate; paresthesia of the skin is the most typical complication and fades away within 3-6 months (132), and fibrous tissue increases in some cases, specifically in women with a male distribution of body fat (132). The characteristics of current treatment scenarios for lymphedema are summarized in Table III.…”
Section: Treatmentmentioning
confidence: 99%
“…Maximum reduction of limb size is usually achieved in the upper limb at 3 months and in the lower limb at 6 months, but it may take longer. For best results, it is advised to wear the garment lifelong [57] . Hoffner et al [58] have shown a mean 5-year postoperative reduction of 117% ± 26% in the limb with lymphoedema compared with the healthy arm.…”
Section: Liposuctionmentioning
confidence: 99%
“…However, because liposuction does not affect the disrupted fluid dynamics of the extremity, the fluid component of the disease is not addressed and a compression garment must be worn continuously following the procedure to control excess fluid accumulation and maintain volume reduction. 30 In properly selected patients, liposuction can provide excellent long-term results with both a decrease in limb volume and decreased infection rates (►Fig. 8).…”
Section: Ablative Surgical Techniquesmentioning
confidence: 99%